Bank float in a new payments system: a study of the implications for commercial banks of a reduction of float as a result of payment system innovations - Carter H. Golembe Associates; American Bankers Association ([New York, American Bankers Association], 1971)
This book contains some of the bank's float and payment system derivation. It examine the trends in the management of the bank's payment system.
Submitted to the Economics Task Force of the Monetary and Payments System Planning Committee.
asm; 04/03/19
Loans
Keywords: Check float